Management of desert rose tetraniquid mites (Adenium obesum Forssk. Roem. & Schult) with entomopathogenic fungi (Research, Society and Development, 2020)
The objective of this study was to evaluate the efficiency of the entomopathogenic fungi Isaria sp. and Beauveria sp. in the control of dust mites in a commercial nursery located on Mosqueiro Island, Belém-PA. The experiment was carried out with the random selection of 36 plants of A. obesum with characteristics of mite infestation. The methodological procedures were based on a qualitative and quantitative analysis for the collected data. The bioassay consisted of 4 treatments with 8 replications, with a completely randomized design. The treatments were applied on the plants to the point of runoff. The results obtained were efficient in controlling mites in desert rose plants, showing that the fungi Beauveria sp and Isaria sp. have high pest control capacity, superior to control with chemical mite killer, standard treatment. Therefore, the fungi Isaria sp. and Beauveria sp. are effective in monitoring mites in desert roses (Adenium obesum Forssk. Roem. & Schult), making the ornamental plant trade an ecologically correct method for the successive use of chemical mites, which can cause resistance to mites and cause negative impacts on man and the environment.